A Case Study Of Toyota Motor Corporation - Louis, Maryann (2005)
The case study comprises of 2 parts. The fisrst part is the case writing which discusses manay elements of the Toyota Motor Corporation. The Second part of the case study moves into a more complicated discussion and analysis of the company.